Transition for Pupils with Special Educational Needs Implications for Inclusion Policy and Practice - Shevlin, Michael; McGuckin, Conor; Scanlon, Geraldine; Barnes-Holmes, Yvonne (Peter Lang Ltd, International Academic Publishers, 2019)
Moving from primary to post-primary school and moving from post-primary to further/higher education pose significant challenges to many young people. Both transitions force young people toward greater personal autonomy, self-awareness and ideally self-efficacy. For students with Special Educational Needs and/or Disabilities (SEND), these challenges are potentially greater, and continuity in, or access to new, support may be necessary to facilitate these transitions in a manner that gives all students equal opportunities for taking charge of their own lives, including their education. The existing empirical literature on the transitions of students with SEND at these levels is limited.　This book reviews the　conceptual, policy and　research evidence on young people's experiences of these transitions. The book also reports on new research conducted with young people with SEND and relevant stakeholders (including parents, educational professionals and voluntary agencies)　involved in　these transitions in Ireland. In so doing, the　book provides a framework of evidence-based practice that can enable schools and professionals to develop effective and inclusive transition policies and programmes.
Keywords: integrovaná výchova a vzdělávání; děti se zdravotním postižením; sociálně ohrožené skupiny; speciální pedagogika; integrated education; children with disabilities; people with social disabilities; special education; elektronické knihy; electronic books